Human Capital Development via Management by Projects - Piwowar‑Sulej, Katarzyna (Edukacja Ekonomistów i Menedżerów, 2013)
The article presents a brief characteristics of the main ways of human capital development and shows the concept of management by projects (MBP) as a tool for this development. The author based the article on her analysis of specialist literature in the area of management and pedagogy as well as the results of interviews conducted with members of the project teams from a clothing industry company. It was found that the implementation of MBP has a direct impact on the sphere of employee trainings and promotion. Consequently, MBP has an influence not only on the development of human capital components such as knowledge and skills, but also on the motivation.